Collecting Smart Meter Data via Public Transportation Buses - Bilgin, Bilal Erman; Baktir, Selcuk; Gungor, Vehbi Cagri (Inst Engineering Technology-IET, 2016)
With advances in technology, wireless sensor networks (WSNs) have found new applications and their popularity has increased dramatically. In several applications, WSNs have the potential to replace wired data communication systems, e.g. in vehicular ad hoc networks (VANETs) they are the natural option for data communication. WSNs are also proposed for data communication in the emerging smart grid. In this study, the authors merge these two application domains, i.e. VANET and smart grids, and propose a novel solution for effective smart grid data communication. The authors' proposed scheme achieves the task of collecting data from smart meters by utilising VANETs. Using network simulator-2 and with different routing protocols, the authors have performed simulations and shown the efficacy of their scheme in terms of average end-to-end delay and delivery ratio.
Baktir, Selcuk/0000-0002-3478-5200; Bilgin, Bilal Erman/0000-0001-6928-4302
Keywords: Public Transport; Smart Meters; Wireless Sensor Networks; Vehicular Ad Hoc Networks; Routing Protocols; Traffic Engineering Computing; Wireless LAN; Smart Power Grids; Smart Meter Data Collection; Public Transportation Buses; WSN; VANET; Smart Grid Data Communication; Network Simulator-2; Average End-to-End Delay; Delivery Ratio